Analysis of dentoalveolar trauma incidents treated in the emergency services department at a healthcare teaching institution in Medellin (Colombia) 2007-2012 (2014)
Introduction: dental trauma is considered a dental emergency and it occurs frequently, especially among young people. The aim of this research was to analyze dentoalveolar trauma incidents treated in the emergency services department of a university clinic in the city of Medellin (Colombia), between 2007 and 2012. Methods: this was a retrospective, descriptive study in which 7.555 clinical histories were revised, the final sample comprising the 549 cases that met inclusion and exclusion criteria. Results: of all causes for consultations, 7,3% were due to dentoalveolar trauma; most patients seeking treatment were females (53,2%). The population aged between 11 and 20 was the most affected (18,4%). Falls and sporting activities caused 15,1% and 6,7% of accidents respectively. Conclusion: dentoalveolar trauma is a common occurrence in emergency dental treatment.